2011
DOI: 10.3892/ijmm.2011.645
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in MyD88 adaptor-like are associated with atopic dermatitis

Abstract: Abstract. Toll-like receptors (TLRs) are important pathogenassociated molecular pattern recognition receptors involved in initiating immune responses. The adaptor protein Myd88 adaptor-like (Mal), involved in signaling downstream of TLRs, plays a crucial role in mediating NF-κB activation. The association of Mal polymorphisms with allergic diseases has not previously been defined. The objective of this study was to detect polymorphisms in the Mal gene and to investigate their association with allergic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Moreover, the mutation of another residue (E132) that is close to the AB loop also led to moderately attenuated NF-κB activation in the present study. Similarly, it has been reported that the natural variant E132K leads to a loss of function of Mal [31]. Furthermore, we found that the D87A mutation, which is located in the first βA strand of Mal-TIR near the AB loop, caused severely attenuated NF-κB signaling.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Moreover, the mutation of another residue (E132) that is close to the AB loop also led to moderately attenuated NF-κB activation in the present study. Similarly, it has been reported that the natural variant E132K leads to a loss of function of Mal [31]. Furthermore, we found that the D87A mutation, which is located in the first βA strand of Mal-TIR near the AB loop, caused severely attenuated NF-κB signaling.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, several studies have associated natural variants of Mal with various infectious diseases [30], [31], [32], [42], . To further understand the molecular mechanism underlying these associations in the Mal-TIR mutants D96N and S180L, we determined the crystal structures of these mutants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations